Pica (Allotriophagy): An Underestimated Risk Factor for Severe Leptospirosis (Weil's Diseases)? Report of a Leptospira Septic Shock Successfully Managed with ECMO - Adam Fabiani; Eugenia Dal Bo; Stefano Di Bella; Marco Gabrielli; Alessandro Bologna; Umberto Albert; Gianfranco Sanson (MDPI AG, 2021)
Leptospirosis is a zoonosis caused by infection with pathogenic strains of the bacterium Leptospira. The disease can be complicated by pulmonary hemorrhages and acute respiratory distress syndrome, with the mortality rate increasing to 51-100%. We report the case of a 37-year-old man who was admitted to the emergency department with a 6-day history of fever, weakness, vomiting and diarrhea, followed by jaundice. On admission, he presented leukocytosis, thrombocytopenia and acute liver and kidney injuries. His clinical course was critical, as it was immediately complicated by sepsis and severe respiratory failure, requiring haemodialysis, mechanical ventilation and broad-spectrum antibiotic therapy. In the following days, a veno-venous extracorporeal membrane oxygenation (VV-ECMO) was started due to a dramatic deterioration in respiratory function; 20 h later, it was switched to veno-arterial ECMO because of refractory cardiogenic shock. Hantavirus or Leptospira infection etiology was suspected, so penicillin G and methylprednisolone were initiated as an empirical therapy and subsequently confirmed after a laboratory diagnosis of leptospirosis. Although the clinical course was further complicated by hemorrhagic pneumonia, a gradual, full recovery occurred, and the patient was discharged from the hospital. After excluding other sources of contact with Leptospira-infected material, an unsuspected abnormal eating behavior was identified as the most probable cause of the patient's Leptospira infection.